Rainwater harvesting augmentation of domestic water supply in Honiara, Solomon Islands. Issue 1 (2nd January 2016) - Quigley, Nicholas; Beavis, Sara G.; White, Ian
Abstract: Secure and sanitary water supply is essential for human health and well-being. The challenges in meeting this demand are great in Small Island Developing States where water resources may be limited due to social and environmental constraints. In Honiara, Solomon Islands, a number of factors have constrained access to fresh water including: rapid population growth and urbanisation; neglected water infrastructure; the ethnic tensions; water tariff increases of 170% in the past 3 years; sole reliance on groundwater; and poor supporting electrical infrastructure. Within this context, the case for using rainwater tanks as either a predominant source or for augmentation of existing domestic water supply has been explored. The effect of historical drought events on rainwater tanks has been examined. A water balance model has been developed and various household scenarios reviewed to determine the reliability of domestic rainwater tanks over a 28-year period. The development of this model has highlighted both opportunities and limitations in Honiara that can be used to inform decision-makers and planners in water resources management.